Development Of The IPPEKA Management Model To Produce Graduates As Agrosociopreneurs In Vocational Education (Journal of Namibian Studies : History Politics Culture, 2023)
The low quality of human resources causes the unemployment rate in Indonesia to increase. The high unemployment rate reflects that until now the quality of graduates has not been able to meet the demands of the world of work. The aim of this research is to develop the IPPEKA management model to produce graduates as agrosociopreneurs. The research method uses a combination of the Sequential Explorataory Model, the research method used first is the qualitative method and the second order is quantitative. The sample in this study were Medan Polbangtan students with a total of 100 students. The research results show that there is an increase in students' interest in entrepreneurship and being able to change their mindset which was initially oriented towards becoming civil servants, working in companies or more dominantly becoming job seekers. Various activities or programs are designed to build student character both moral character and performance character. However, after the coaching and character development that was applied to students were able to change the mindset where the entrepreneurial spirit had been instilled in students by integrating entrepreneurial activities into the learning process and extracurricular activities so that students had started doing business on a small scale, especially in the agricultural sector both in the upstream and in the upstream sector. downstream sector.